An Approach to Improve the Misalignment and Wireless Power Transfer into Biomedical Implants Using Meandered Wearable Loop Antenna. (20th February 2021) - Kod, Muayad; Zhou, Jiafeng; Huang, Yi; Hussein, Muaad; Sohrab, Abed P.; Song, Chaoyun
Abstract : An approach to improve wireless power transfer (WPT) to implantable medical devices using loop antennas is presented. The antenna exhibits strong magnetic field and dense flux line distribution along two orthogonal axes by insetting the port inside the antenna area. This design shows excellent performance against misalignment in the y -direction and higher WPT as compared with a traditional square loop antenna. Two antennas were optimized based on this approach, one wearable and the other implantable. Both antennas work at both the ISM (Industrial, Scientific, and Medical) band of 433 MHz for WPT and the MedRadio (Medical Device Radiocommunications Service) band of 401–406 MHz for communications. To test the WPT for implantable medical devices, a miniaturized rectifier with a size of 10 mm × 5 mm was designed to integrate with the antenna to form an implantable rectenna. The power delivered to a load of 4.7 kΩ can be up to 1150  μ W when 230 mW power is transmitted which is still under the safety limit. This design can be used to directly power a pacemaker, a nerve stimulation device, or a glucose measurement system which requires 70  μ W, 100  μ W, and 48  μ W DC power, respectively.